“Beyond Morality.” Discourse on Homosexuality in Croatian Newspapers from the Sociosemiotic Perspective: Comparison of Two Periods - Sandra Antulov; Mislava Bertoša ([sic])
This paper aims to analyse and compare two newspaper articles dealing with issues of gay people in Croatia that were published in two different periods. The first article dates from the early 1990s, which was the starting point of contemporary Croatian gay activism. The second was published 16 years later, in 2008, within a different social and political context. It was the period when gay activism in Croatia had already reached some of its aims, and when the discourse on homosexuality had become more visible and acceptable in the media. In comparing these two periods, we focus on surface differences between two newspaper articles, while at the deep level we look for similarities and unchanged features. Our perspective is sociosemiotic – it will be explained in more detail in the next section. For now, it needs to be stressed that we integrate both verbal and visual elements of the two articles, explore differences and similarities in the discursive strategies of constructing and representing homosexuality, and analyse differences and similarities in aspects of utterances and utterance actors involved.